2019
DOI: 10.1021/acsami.8b18795
|View full text |Cite
|
Sign up to set email alerts
|

Poly(3-alkylthiophene)-block-poly(3-alkylselenophene)s: Conjugated Diblock Co-polymers with Atypical Self-Assembly Behavior

Abstract: Understanding self-assembly behavior and resulting morphologies in block co-polymer films is an essential aspect of chemistry and materials science. Although the self-assembly of amorphous coil−coil block co-polymers is relatively well understood, that of semicrystalline block co-polymers where each block has distinct crystallization properties remains unclear.Here, we report a detailed study to elucidate the rich selfassembly behavior of conjugated thiophene−selenophene (P3AT-b-P3AS) block co-polymers. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 63 publications
0
31
0
Order By: Relevance
“…At this point, it is interesting to deduce the effects of the P3HT/P3BS block ratio and thermal annealing temperature on the microphase-separated or cocrystalline structures of these P3HT- b -P3BS BCPs. It is reported that polymers possess similar structures, potential energies, and crystallization kinetics may form cocrystals, , and only several examples of polymer cocrystals have ever been reported to date. ,, For the three P3HT- b -P3BS BCPs casting from toluene solution, they exhibit microphase-separated structures composed of sole P3HT crystalline domains or individual P3HT and P3BS crystalline domains depending on the block ratio of P3HT/P3BS (Figure d). After 200 °C-annealing these BCP samples, P3BS form II changed to form I of higher crystallinity and larger d 100 -spacing in HT55BS45 and HT42BS58.…”
Section: Resultsmentioning
confidence: 99%
“…At this point, it is interesting to deduce the effects of the P3HT/P3BS block ratio and thermal annealing temperature on the microphase-separated or cocrystalline structures of these P3HT- b -P3BS BCPs. It is reported that polymers possess similar structures, potential energies, and crystallization kinetics may form cocrystals, , and only several examples of polymer cocrystals have ever been reported to date. ,, For the three P3HT- b -P3BS BCPs casting from toluene solution, they exhibit microphase-separated structures composed of sole P3HT crystalline domains or individual P3HT and P3BS crystalline domains depending on the block ratio of P3HT/P3BS (Figure d). After 200 °C-annealing these BCP samples, P3BS form II changed to form I of higher crystallinity and larger d 100 -spacing in HT55BS45 and HT42BS58.…”
Section: Resultsmentioning
confidence: 99%
“…[64][65][66][67] Interestingly, high-curvature morphologies can be induced by synthesizing block copolymers comprising P3AT and P3AS components. Work from our group has shown the synthesis of patchy nanofibers formed from the chain-folding of poly(3-dodecylthiophene) (P3DDT) blocks around poly(3dodecylselenophene) (P3DDS), where these high-curvature morphologies are accessed with increasing degree of polymerization (N) [68,69] (Figure 2a). Notably, decreasing phase segregation was found to increase charge mobility, with films exhibiting the cocrystallization having moderate hole mobilities as high as 1.2 × 10 −2 cm 2 V −1 s −1 .…”
Section: Linear Block Circular and Star Copolymersmentioning
confidence: 99%
“…However, when N is increased, thiophene and selenophene blocks co-crystallize into fibers (N = 50-60) and patchy fiber (N > 80). Field-effect transistors testing showed that co-crystalline fibers have the best device performance [114].…”
Section: Degree Of Polymerization (N)mentioning
confidence: 99%
“…This probably is because the miscibility of P3HT and PFTBT has become better, resulting in weaker phase separation [14] . [114]. Copyright American Chemical Society).…”
Section: Side Chain Engineeringmentioning
confidence: 99%